2003
DOI: 10.1007/s10024-001-0276-y
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset and Recurrent Neonatal Group B Streptococcal Disease Associated with Breast-milk Transmission

Abstract: The purpose of the study was to determine the epidemiological relationships in three unrelated cases of neonatal late-onset Group B streptococcal (GBS) disease and maternal breast-milk infection with GBS. All deliveries were by cesarean section; case 1 was at term, and cases 2 and 3 were at 32- and 33-wk gestation, respectively. Case 1 relates to a mother with clinical mastitis and recurrent GBS infection in a 20-day-old male infant. Following antibiotic therapy and cessation of breast-feeding, the infant reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 14 publications
0
52
1
1
Order By: Relevance
“…A simultaneous therapy of the newborn is often necessary. After fever and clinical symptoms have resolved, breastfeeding can be continued [15].…”
Section: Abscesses and Complicationsmentioning
confidence: 99%
“…A simultaneous therapy of the newborn is often necessary. After fever and clinical symptoms have resolved, breastfeeding can be continued [15].…”
Section: Abscesses and Complicationsmentioning
confidence: 99%
“…However, human milk is not sterile and can be a vehicle for commensal or pathogenic microorganisms derived from the mother or the environment during collection, storage and handling of the milk [11]. Organisms linked to human milk-induced infections include Staphylococcus aureus , group B streptococci, Escherichia coli , Serratia spp., Pseudomonas spp., Salmonella spp., HIV and cytomegalovirus [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Cases reporting neonatal late and recurrent group B streptococcal disease associated with raw maternal milk are rare, and there are few studies in which genetic evidence is proposed for this scenario [2,7,13]. In our case, not only was total DNA macrorestriction analysis conducted, showing indistinguishable patterns for the six isolates, but additional genetic analysis also revealed that the GBS isolates belonged to a particularly virulent clone shown to produce more extracellular neuraminidase [8].…”
Section: Discussionmentioning
confidence: 67%